Media Usage of Facebook in the Health Promotion Programme of Puskesmas - Saputra, Angga; Darmawati, Darmawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Based on the development of the potential of Facebook Social Media Implementation in Kuala Kampar Community Health Center as an information dissemination medium. In this study, the Kuala Kampar Sub-District Health Center has successfully implemented Facebook Social Media as an effective means of disseminating health information. The Health Center's Facebook account has been recognized by the surrounding community, as evidenced by high responsiveness and growth in the number of followers. This is in line with the Health Center's mission to improve community health and human resource competency.This study aims to determine the implementation of social media usage in promotional programs at the Kuala Kampar Sub-District Health Center, Pelalawan Regency. By providing health information through the Facebook platform, the Health Center contributes positively to raising awareness and knowledge of community health sustainably. Using a qualitative method that is informative, relevant, and easily accessible, Referring to Harold D. Lasswell's communication theory, this study clearly explains who the communicator is, what message is conveyed, the media used, who the audience is, and the resulting effects. The result of this study is that the Kuala Kampar Sub-District Health Center has successfully utilized Facebook as a health promotion medium. They effectively deliver information to their audience and receive positive responses from the community. Despite facing technical constraints such as network issues, the enthusiasm to continue educating the community remains high. The Kuala Kampar Sub-District Health Center has succeeded in being an example of utilizing social media for public health purposes.